Hidrolisis Mikroalga Tetraselmis Chuii Menjadi Glukosa Menggunakan Solvent H2SO4 Dengan Variasi Waktu Hidrolisis - Fajrina Qaishum; Amun Amri; Syelvia Putri Utami (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Indonesia is maritime countries with high marine biodiversity. Mikroalgae is marine biota which has an important role in an ecosystem water and it has the chemical composition such as, high carbohydrate, protein and lipid. Tetraselmis chuii is green microalgae that contains cellulose and hemicelluloses, which adequate were converted into glucose. Glucose is one of building compound for producing hydroksimetilfurfural, levulinat acid, formic acid, bio battery, bioethanol, etc. Glucose can be produced by hydrolyzing microalgae with dilute sulfuric acid use a solvent. Microalgae was dissolved in diluted sulfuric acid then heated at 100oC. The purpose of this research were obtained operation condition for biomass loading and hydrolysis time to glucose production. Tetraselmis chuii which biomass loading 3,5 gram disssolved in dilute sulfuric acid 1% during 10, 20, 30, 40 and 50 minutes. The result show that the highest concentration of glucose was obtained 7,27 g/L in biomass loading by using 3,5 gram of Tetraselmis chuii for 30 minute at 100oC.Keywords: dilute sulphuric acid, glucose, hydrolysis, microalgae, cellulose